The Perceived Role of Teachers in Resolving Conflicts Between Students: Reflections on Effectiveness and Intervention - Abílio Afonso Lourenço; Maria Olímpia Almeida Paiva (Journal of Advanced Research in Education, 2025)
This article proposes a reflection on the perceived role of teachers in managing conflicts between adolescents in the school context. The central focus is on how educators perceive and interpret conflicts between students, and how this perception influences their resolution strategies and the effectiveness of interventions. Through a theoretical review, the nature of conflict in the school environment is explored, addressing the different types and levels of conflict (intrapersonal, interpersonal, intragroup, and intergroup) and their causes, such as social, emotional, and cultural factors. Furthermore, conflict resolution strategies based on existing theories are discussed, with an emphasis on the active role of teachers in mediation, prevention, and resolution of disputes. The reflection also includes an analysis of the consequences of unresolved conflicts, both for the students involved and for the school environment in general. Based on teachers’ perception of conflict and their role in mediation dynamics, the article argues that a conscious and informed approach can increase the effectiveness of pedagogical intervention. The article concludes with recommendations on how to improve teacher training in conflict management, aiming to promote a more harmonious and inclusive school environment. This reflection seeks to contribute to a deeper understanding of the interaction between teachers, students, and conflict in the educational context.